Factors affecting musical band performance in Kuala Lumpur / Abdul Azim Talhah - Talhah, Abdul Azim (2016)
The purpose of the study was to detemine the factors aims to achieve a deeper understanding of this situation where those who are well-trained by the music academy did not stand out or are not able to win a music competition compared to those individuals or bands that has no musical background. This study has been conducted in Kuala Lumpur bands competition. The samples for this study were 50 individuals from band members in Kuala Lumpur bands competition range from 18 years old and above. From this study, it can be concluded that main reasons the individuals or bands participate with competition able to win in band competition with no musical background.